Imaging-detected acute muscle injuries in athletes participating in the Rio de Janeiro 2016 Summer Olympic Games. Issue 7 (7th December 2017) - Crema, Michel D; Jarraya, Mohamed; Engebretsen, Lars; Roemer, Frank W; Hayashi, Daichi; Domingues, Romulo; Skaf, Abdalla Y; Guermazi, Ali
Abstract : Background: Acute muscle injuries in elite athletes are responsible for a large portion of time loss injuries. Aim: To describe the frequency, the anatomic distribution, and severity of imaging-detected acute muscle injuries among athletes who competed in the Rio de Janeiro 2016 Summer Olympics. Methods: We recorded all sports injuries reported by the National Olympic Committee medical teams and the Organising Committee medical staff during the 2016 Summer Olympics. Imaging of acute muscle injuries was performed at the IOC's polyclinic within the Olympic Village using ultrasound and 3.0 T and 1.5 T MRI scanners. The assessment of images was performed centrally by three musculoskeletal radiologists. The distribution of injuries by anatomic location and sports discipline and the severity of injuries were recorded. Results: In total, 11 274 athletes from 207 teams were included. A total of 1101 injuries were reported. Central review of radiological images revealed 81 acute muscle injuries in 77 athletes (66% male, mean age: 25.4 years, range 18–38 years). Athletics (track and field) athletes were the most commonly affected (n=39, 48%), followed by football players (n=9, 11%). The majority of injuries affected muscles from lower limbs (n=68, 84%), with the hamstring being the most commonly involved. Most injuries were grade 2 injuries according to the Peetrons classification (n=44, 54%), and we found 18 injuries exhibiting intramuscular tendon involvement on MRI. Conclusion: Imaging-detected acute muscle injuries during the 2016 Summer Olympics affected mainly thigh muscles in athletics disciplines.